The heart failure pandemic: The clinical and economic burden in Greece. (15th January 2017) - Stafylas, P.; Farmakis, D.; Kourlaba, G.; Giamouzis, G.; Tsarouhas, K.; Maniadakis, N.; Parissis, J.
Abstract: Background: The objective of this study was to identify the epidemiological and clinical characteristics of heart failure (HF) patients in Greece as well as the economic burden and the distribution of costs for the management of the disease. Methods: Eight Greek secondary and tertiary cardiology centres from different cities have participated in a prospective, observational survey, the ESC HF Pilot Survey. 307 patients with HF, 177 hospitalised and 130 outpatients, have been recruited and monitored for 12 months. Clinical and epidemiological data, along with data on mortality, hospitalisations and health care resources used have been collected. The economic evaluation was conducted from the social security system perspective. Results: The annual mortality rate was 24.3% for the hospitalised patients vs 7.7% for the outpatients (P < 0.001) and the annual rehospitalisation rate was 42.9% vs 19.2% respectively (P < 0.001). Kaplan–Meier analyses revealed that patients with kidney dysfunction, S3 gallop and higher NYHA class have a significantly worse survival. The mean annual economic burden of the social security system per HF patient was estimated at €4411 ± 4764. About two thirds of this cost is due to in-patient care. Conclusions: Despite the progress in the management of the disease, about one in four hospitalised patients dies and four in ten are rehospitalised in less than one year. Moreover, the disease imposes a significant economic burden for the social security system and national economy. Their findings suggest that there is still need of more effective drug treatment and efficient disease management programs focused in the reduction of the hospital admissions.